Análisis de las principales causas de errores de posicionamiento de hueco en el Campo Rubiales de Ecopetrol (2019)
This project analyzes the principal causes of wellbore positioning errors in Ecopetrol S.A.’s horizontal wells in Rubiales Field. First of all, a geological and theoretical framework will be done. The geological framework describes Llanos Orientales’ stratigraphy and structural composition, while the theoretical framework provides the reader with enough information to fully understand this project. In second instance, each cause will be analysed. Firstly, the quality of Pacific Rubiales’ and Ecopetrol S.A.´s database concerning Ground Level and Rotary Table Elevation will be revised. Next, the wells will be created using the software COMPASS, this will allow to evaluate the operational impact that survey stations’ frequency has in wellbore positioning. Finally, the geosteering tools used in this field will be compared to choose the best one. Lastly, a financial framework about the different geosteering tools used in the field and survey station´s frequency will be made applying NPV and CBA. This framework will show the economic benefits caused by decreasing survey stations’ frequency.